Analisis Sistem Akuntansi Pembelian Barang di Whiz Residence - Shofiyah Nursholikah; Erry Andhaniwati (Economic Reviews Journal, 2024)
A hotel is a business that provides accommodation services, food and beverage providers, as well as other service facilities, all services intended for the general public, which are managed on a commercial basis. The purpose of this research is to understand and determine the effectiveness of the accounting system process for purchasing goods at Whiz Residence. The method used is a qualitative method and uses primary data sources from Whiz Residence. The results of this research are that the purchasing accounting system process carried out at Whiz Residence according to standard operational procedures is not effective and efficient and there are several work problems in the cost control and receiving sections handled by the purchasing section. The conclusion of this research is that a lack of human resources results in the purchasing accounting system process not running efficiently. Suggestions that can be conveyed are that Whiz Residence should add additional human resources to improve performance.